The prevalence of detectable blood alcohol concentration among unnatural deaths in Northern Thailand - Siripun Narongchai (2018)
Background: Alcohol is the most common substance abused. It causes many kinds of injuries and death from accidents, homicides, suicides and sudden unexplained natural death (SUND). Traffic accidents especially, have a very close correlation with alcohol concentration levels in the body. Material and Method: In the present study, there were 1,138 corpses who were sent for autopsy at Chiang Mai University from January to December 2003, in which 78.4% of these cases suffered unnatural death. Results: The incidence of accident was 64.7%, homicide was 22.3% and suicide was 13%. The authors used 153 corpses as a sample. In the sample, 74 (48.4%) were from traffic injuries. There was Blood Alcohol Concentration (BAC) detected in 82 (53.6%) of them, and 99% were male. Their age range was 26-35 years in 42.7% of cases, the employees constituted 48%, 57% were married, 52.4% had traffic injuries for a total of 54.9% who experienced accidental death. The BACs in the accident deaths were very high, with 67 (81.7%) having blood alcohol concentrations of more than 50 mg, 58 (70.7%) with more than 100 mg% and only 15 (18.3%) with less than 50 mg%. The highest BAC detected was 396 mg% in a case that did not die of alcohol toxicity. The most common range of BAC in these cases was 151-200 mg% in 20.7% of cases. Conclusion: Alcohol is one of the most common associations with unnatural death in Thailand. From the present study the authors found alcohol associated with drugs such as diazepam and chlorpheniramine etc.